A novel approach to determine the surface area of buckspoor spider webs and other irregular-shaped two-dimensional objects - Venter, Christiaan; Haddad, Charles Richard; Codron, Daryl (Elsevier, 2022)
Arising from the practical need to determine the surface area of the buckspoor spider webs of Seothyra schreineri, an approach for area determination was developed based on image processing. The method rendered results that were considered valid and reliable. Aside from the present application to determine the surface area of a spider web, this approach could potentially be used to accurately determine the area of any two-dimensional shape. For each web's photograph: The boundary of the web was outlined. Seeded region growing was used to segment the image into a web region and a background region. The area of the web was determined as a pixel count, and then converted to mm2.
Keywords: Burrow; Nama Karoo; Peripheral length; Pixels; Silk